Healthy adolescents free of anemia in iyok village, north bolaang mongondow regency - Wulansari, Meinita; Anti Makalungsenge, Asri; Stevanie, Michelle; Injilia Febiola Dommits, Tesalonika; Tinumbia, Sumaya; Husna Laya, Megawati; Ngabito, Engreta; Umagapi, Ermi (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2025)
Adolescents are an age group that plays a role in stunting prevention efforts. The increasing incidence of anemia is one of the factors causing the high incidence of stunting. The visitor program is the implementation of PHBS education in the elementary school community and health screening for the general public. The results of observation show the lack of role of adolescent girls in preventing stunting, so it is necessary to accompany them to obtain increased knowledge and skills in accompanying adolescents to avoid stunting. The method of service activities is the assistance of 20 adolescents, consisting of three stages, namely the first stage of providing education and socialization on anemia prevention, the importance of Blood Supplement Tablets (TTD), how to consume, demonstration of anemia detection, pre-intervention Hb examination. The first stage is pretest and posttest on adolescents. The second stage, post-intervention Hb examination, the third stage is the administration of blood-boosting tablets. The participants of this PHBS educational activity are 6th grade students totaling 26 students. From the results of initial observations before being given education, there are still some students who do not understand and know how to maintain their hygiene in terms of washing their hands properly and correctly. The results of the next supporting activity are that this health examination aims to carry out public health screening in the form of cholesterol, uric acid, blood sugar and blood pressure. This activity was attended by 17 people from Iyok village, most of whom were women. The results of the examination showed that most people had good health conditions